2013
DOI: 10.1039/c3ra45521a
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombogenic properties of a nitric oxide-releasing dextran derivative: evaluation of platelet activation and whole blood clotting kinetics

Abstract: Controlling platelet activation and clotting initiated by cardiovascular interventions remains a major challenge in clinical practice. In this work, the anti-thrombotic properties of a polysaccharide-based nitric oxide (NO)-releasing dextran derivative are presented. Total platelet adhesion, platelet morphology and whole blood clotting kinetics were used as indicators to evaluate the anti-clotting properties of this material. With a total NO delivery of 0.203±0.003 μmol, the NO-releasing dextran derivative (De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 62 publications
(88 reference statements)
1
26
0
Order By: Relevance
“…Incubation was performed at room temperature on a horizontal shaker plate (100 revolutions per minute) for 2 hours with the aim of dispersing coagulation factors produced from activating platelets. These methods are similar to previously used techniques to assess platelet adhesion and activation on various biomaterials 23, 52, 53, 63, 75 . After incubation, samples were fixed with 1% gluteraldehyde and were dried through a series of ethanol treatments.…”
Section: Methodsmentioning
confidence: 95%
“…Incubation was performed at room temperature on a horizontal shaker plate (100 revolutions per minute) for 2 hours with the aim of dispersing coagulation factors produced from activating platelets. These methods are similar to previously used techniques to assess platelet adhesion and activation on various biomaterials 23, 52, 53, 63, 75 . After incubation, samples were fixed with 1% gluteraldehyde and were dried through a series of ethanol treatments.…”
Section: Methodsmentioning
confidence: 95%
“…For this reason, endothelium is one of the most thromboresisitive materials. Consequently, materials that can release NO at a steady-state equivalent to that released by the natural endothelium (0.5 × 10 −10 mol cm −2 min −1 ) [ 15 ], can be a suitable material for making biomedical devices with enhanced antifouling capabilities [ 16 , 17 ]. Liu et al recently demonstrated that the presence of NO significantly reduces the formation of Shewanella woodyi ( S. woodyi ) biofilm by simultaneously down-regulating the cyclase activity and up-regulating the phosphodiesterase activity of the diguanylate cyclase gene ( Sw DGC) (Fig.…”
Section: Strategies For Making Antifouling Biomedical Surfacesmentioning
confidence: 99%
“…Additionally, it has been shown that reactive oxygen species, produced by PEG might modulate the cell response [ 46 ]. For these reasons, alternate hydrophilic polymers such as polyglycerols [ 47 ], polyoxazolines [ 48 ], polyamides [ 49 ], and naturally occurring polysaccharides [ 17 ] have been evaluated for antifouling applications.…”
Section: Strategies For Making Antifouling Biomedical Surfacesmentioning
confidence: 99%
“…Many published methods to investigate the anti-thrombogenic properties of biomaterials focus on studying the early stages of blood clotting, such as protein adsorption, and platelet adhesion and activation. Although they are important to understand the interaction between blood and the implant surface, these studies do not provide significant information about the overall coagulation process (Damodaran et al, 2013;Simon-Walker et al, 2018;Obstals et al, 2018).…”
Section: Thrombogenicitymentioning
confidence: 99%